Beyond empowerment : changing power relations in rural Bangladesh - Costa, Thomas. 1953-; Community Development Library (Dhaka, Bangladesh) (Dhaka : Community Development Library, 1999)
Comparative study of two villages, one in Badolgachi Thana, Naogaon District and the other in Dinajpur District, Bangladesh.
Includes bibliographical references (p. 185-188).
Keywords: Rural development -- Bangladesh -- Badolgachi Thana -- Case studies; Rural development -- Bangladesh -- Dinajpur District -- Case studies